Spatial-temporal distribution and source apportionment of riverine dissolved organic carbon in the Miyun section of the Chaobai River in Beijing, China - Junjie Wang; Xiao Pu; Ruining Zhang; Xunliang Liu; Yuhu Zhang; Jian Wang; Yifan Wang; Mingxue Meng; Siqi Li (Water-Energy Nexus, 2023)
Dissolved organic carbon (DOC) is indicative of water quality in drinking source water and has an impact on drinking water treatment. Exploring occurrence of DOC in drinking source water is of great significance for the drinking water safety in Beijing. This study elucidated spatial-temporal DOC dynamics in the Miyun section of Chaobai River in Beijing of China and identified sources of DOC based on DOC fluorescent spectral characteristics. Results showed that the average riverine DOC concentration was 30.60 mg/L. DOC concentrations in the Miyun section of the Chaobai River were 30.40, 30.24, and 31.09 mg/L in spring, summer and autumn, respectively. DOC concentrations at the three segments of the Miyun section of the Chaobai River (the Chaohe River, the Baihe River and the Chaobai River) were 29.93, 30.29 and 32.57 mg/L, respectively. Land use contributed to DOC variations rather than season and river segment. Significant increases in DOC concentration were observed in river water flowing through farmland and urban areas, and DOC concentration presented the highest after flowing through the farmland area. The results of FI, HIX and BIX showed that DOC mainly came from endogenous sources such as aquatic biological activities, and was less affected by terrestrial inputs. Special attentions ought to be paid on prevention and control of endogenous DOC inputs.